Edukasi Seksual Sebagai Upaya Pencegahan Kekerasan Seksual Pada Anak: Literatur Review - Tiwery, Indah Benita (MOLUCCAS HEALTH JOURNAL, 2022)
Children's age is a very vulnerable age because children's cognitive development is still developing and immature. Children still need assistance so they are more at risk of getting violence, both physically, psychologically, and sexually. The purpose of the literature review is to identify sexual health education as an effort to prevent sexual violence in children. Search articles using 2 databases, namely Google Scholar, and Proquest, Ebsco. Based on the search results obtained 1,838 articles but only 7 articles met the inclusion criteria. From the article, it was found that sexual education had a significant effect on the prevention of sexual violence in children. Sexual education can be given to increase knowledge. To children, it can be done through discussion methods, movements and songs, stories and videos, to parents through lectures and leaflets, to health cadres through the leaflet method. Therefore, promotive efforts in preventing sexual violence through education must continue to be improved. Nurses can play a role in these activities.